BREEDING BIOLOGY OF THE FRESHWATER COPEPODA, llELIODIAPTOMUS VIDUUS (GURNEY) AND ITS PROSPECTS AS LIVEFOOD ORGANISM (Biological Sciences - PJSIR, 2003)
The tropical freshwater copepoda, Heliodiaptomus 1•iduus occur commonly in the peninsular India. This species is comparatively bigger (total mean length of female and male is 2.05 ± 0.09mm and 1.7 ± 0.04mm respectively) than other freshwater diaptomids. Aspects of reproductive biology such as sexual dimorphism, organisation of female and male reproductive system, oogenesis, spermatogenesis and spermatophore formation are described for the first time. Details pertaining to fertilization, embryonic and post embryonic development of this specie is reported. Studies on live span and reproductive potential of this specie indicate continuous breeding with short interclutch period. Importance of the livefood in aquahatcheries  and prospects  of  H.viduus as alternate livefood  to Artemia  nauplii is discussed.